Identifikasi Destinasi Pariwisata Kota Medan Studi Kasus Taman Gajah Mada Medan Kec. Medan Baru - Lubis, Winnie Annisa; Ramadhani, Desy; Wisdianti, Dara (Jurnal Teknik dan Teknologi Indonesia, 2025)
Natural tourist attractions are natural resources that have potential and have an attraction for visitors both in their natural state and after cultivation efforts, while Green Open Space [RTH] is an elongated area/path and/or cluster, whose use is more open, a place to grow. plants, both those that grow naturally and those that are deliberately planted. The method used is a documentary descriptive method using primary data and secondary data. Through the identification of Gajah Mada Park in Medan City, it is hoped that it can reveal the role of the park in supporting tourist destinations and supporting an increase in the percentage of open green space in Medan City and it is hoped that it can become a proposal for designing Green Open Space. The method used is a documentary descriptive method using primary data and secondary data.